Arabic Curriculum Design in the Merdeka Curriculum from the Perspective of the American Council on the Teaching of Foreign Languages (ACTFL) - Hasyim Asy'ari; Naifah; Cahya Edi Setyawan (Mantiqu Tayr: Journal of Arabic Language, 2024)
This paper aims to analyze the design of the Arabic language learning curriculum in the Merdeka curriculum. Researchers use the ACTFL standard in analyzing the content of the Arabic language curriculum in the aspect of competence and depth of mastery of Arabic formulated in the Merdeka curriculum. The purpose of this analysis is to compare Arabic learning outcomes in the Merdeka curriculum with ACTFL standards used internationally in learning foreign languages. The type of research used is qualitative research with a content analysis approach. Data collection methods with documentation. The data and data sources of this research are the Decree of the Director General of Islamic Education 3211 of 2022 concerning the learning outcomes of Islamic religious education and Arabic for the Merdeka Curriculum in Madrasah. Qualitative content analysis design of the Kripendorff model through the stages of selecting units, determining samples, recording data, reducing data, drawing conclusions, narrating research results. The results showed that the Arabic curriculum in the Merdeka curriculum based on ACTFL is divided into 2 aspects, namely: aspects of language skills and language proficiency levels. Language skills include: 1) language skills (language proficiency and language elements), 2) communication skills: interpersonal communication, presentation communication and interpretive communication, 3) cultural skills. The Arabic language learning curriculum design in the Merdeka curriculum is taught from phase A, the easiest level relevant to the ACTFL standard at the low beginner level and phase F is the highest level relevant to the ACTFL standard at the superior level. Analysis of Arabic learning outcomes in the Merdeka curriculum based on ACTFL standards is at the Novice Low to superior level.